2009
DOI: 10.5194/hessd-6-2961-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Applied tracers for the observation of subsurface stormflow at the hillslope scale

Abstract: Rainfall-runoff response in temperate humid headwater catchments is mainly controlled by hydrological processes at the hillslope scale. Applied tracer experiments with fluorescent dye and salt tracers are well known tools in groundwater studies at the large scale and vadose zone studies at the plot scale, where they provide a means to characterise subsurface flow. We extend this approach to the hillslope scale to investigate saturated and unsaturated flow paths concertedly at a forested hillslope in the Austri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 70 publications
2
34
0
2
Order By: Relevance
“…A detailed description of the Heumöser slope can be found in Lindenmaier et al (2005), Lindenmaier (2008) and Wienhöfer et al (2009). An essential characteristic of the slope is that macropores and soil pipes are able to generate fast breakthrough curves of a tracer at a spring and on a cut-bank near a hiking trail (see Fig.…”
Section: Simulationsmentioning
confidence: 99%
See 4 more Smart Citations
“…A detailed description of the Heumöser slope can be found in Lindenmaier et al (2005), Lindenmaier (2008) and Wienhöfer et al (2009). An essential characteristic of the slope is that macropores and soil pipes are able to generate fast breakthrough curves of a tracer at a spring and on a cut-bank near a hiking trail (see Fig.…”
Section: Simulationsmentioning
confidence: 99%
“…Wienhöfer et al (2009) concluded that the processes are controlled by complex structures (macropores, soil pipes, soil layers) and their interactions. The soil matrix was classified as a silty clay loam and silt loam, with a shallow topsoil (∼10 cm) Wienhöfer et al (2009) were mainly cracks and soil pipes with diameters up to several cm. The macropore walls had dark coatings, indicating their temporal persistence.…”
Section: Simulationsmentioning
confidence: 99%
See 3 more Smart Citations